Multistable vibration energy harvesters: Principle, progress, and perspectives - Zhou, Shengxi; Lallart, Mickaël; Erturk, Alper (Journal of sound and vibration, 2022)
•The progress of multistable vibration energy harvesters (MEH) is reviewed.•Governing models and approximate analytic methods are introduced.•Design, experiment, influence mechanism and optimization are illustrated.•MEHs in rotational motion, wind energy harvesting, etc, are stated.•Critical challenges, perspectives for future research directions about MEHs are presented. Vibration energy harvesting is a process by which ambient mechanical energy from environment or host structures is converted into usable energy (usually, but not always, electrical energy). This technology is considered to be a relatively new method for supplying sustainable energy to low-powered sensor networks and electronic devices. Various vibration energy harvesters utilizing piezoelectric, electromagnetic, electrostatic, and triboelectric energy conversion mechanisms were designed and tested to achieve this goal. Meanwhile, one key challenge of such approaches results from their response to the input excitation characteristics, especially in terms of frequency variation. To address that challenge, multistable characteristics commonly exist in mathematical models and physical devices, which can be used for designing vibration isolators, compliant mechanisms, morphing structures, circuits, filters, etc. Currently, multistable vibration energy harvesters have received increasing attention because of their rich nonlinear dynamic characteristics which show benefit for improving efficient vibration energy harvesting bandwidth, i.e. frequency-wise robustness. This paper aims to provide a comprehensive review of the state-of-the-art progress of multistable vibration energy harvesters.